Hubungan Timbang Terima Metode SBAR Dengan Kepuasan (Pasien The Relationship Between Handover Using SBAR Communication Method And Patient Satisfaction): - - Wahyuningsih Safitri; Atiek Murharyati; Tri Astuti (Rena Cipta Mandiri, 2025)
Background: Handover with SBAR Method (Situation, Background, Assessment, Recommendation) is an effort to improve communication about patient condition. Good SBAR communication can improve patient satisfaction. Research Objective: To determine the relationship between handover with SBAR method and patient satisfaction at PKU Muhammadiyah Hospital, Sukoharjo. Research Method: This study used quantitative research method, analytical survey design and cross sectional approach. Purposive sampling technique, involving 156 patients. Results: Spearman Rank test showed p value 0.000 <0.05 so Ho was rejected. Conclusion: There is a relationship between handover with SBAR method and patient satisfaction at PKU Muhammadiyah Hospital, Sukoharjo.